ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PREFERENSI DEPOSITO DI KOTA MALANG (STUDI PADA BANK UMUM SYARIAH DAN BANK UMUM KONVENSIONAL) - Pratama, Ricky (Jurnal Ilmiah Mahasiswa FEB, 2016)
To know people time deposit choice, we have to know preference determining factors. Time Deposit between Shareea Bank is different with Conventional Bank.By using Logistic Regression (LOGIT), this study observe determining factor which influence time deposit preference in Malang Variable include profitability, knowledge, service and environment. Results is majority of people which age between 16-25 want to have time deposit in shareea bank. Profitability, knowledge and environment influence time deposit preference. Keywords: Time-Deposit, Preference, Regression Logistic, Malang